Where are the digital natives? Identifying and mapping digital literacy skills of students and teachers in an international college - Prescott, T (2015)
This research aimed to identify and map the digital literacy skills of students and teachers in an international college. Digital literacy is increasing in importance: effective digital literacy skills now determine the level of access to an individual’s economic future and full digital citizenship. Conversely, a lack of digital skills excludes individuals from digital life, including being able to contribute to the discourses that are shaping their future. In the college, the contact time for teaching basic digital literacy skills to students has been cut by 50%. In addition to this, the weekly hours for providing training and mentoring support for teachers to develop their digital literacy, through the Advanced Practitioner team, have been cut by 50%. Therefore there was a need to find out how the digital literacy skills of students and teachers are developing in this environment. This study firstly carried out an extensive review of the current empirical research in this field before proceeding with three action research cycles, which involved 69 research participants: 24 students and 45 teachers. The data collection methods included 5 online student learning journals, an online survey (skills audit) for teachers and feedback sheets gathered from a focus group of teachers. Collaboration with teachers to develop the action research cycles was a key feature of the study and Activity Theory was used as an additional analytical lens. The findings revealed that students have limited access to opportunities to develop their digital literacy in lessons. They are asking for help to develop their digital literacy skills and knowledge, whilst acknowledging that they have gaps in their knowledge. Furthermore, they want teachers to develop their digital expertise so that they can collaborate with them to help them navigate the digital world. The findings of the skills audit revealed that with a few exceptions, generally teachers in the college only feel confident in the basic use of learning technologies. The findings evidence that digital literacy is an important issue that has been overlooked in this setting, with ramifications for how the college and the wider organisation are perceived by potential students/future customers. The key recommendation is for a strategic approach to the issue of digital literacy to be adopted by the college/wider organisation, which must include: improving access to learning technologies for students by further embedding digital literacy across the curriculum; plus upskilling teachers by providing a comprehensive time-tabled programme of digital literacy training.